Simbol-Simbol Bahasa Bali pada Pupulan Puisi "Adi Bulan" Karya I Putu Wahyu Santosa: Kajian Semiotika Sastra dan Relevansinya dalam Pembelajaran Apresiasi Puisi Bali Modern - Wahyuni, Ni Putu Eka (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
Although Modern Balinese poetry has been taught at various levels of education and is widely known by the public, understanding of the Balinese symbols contained within it remains suboptimal. In fact, the beauty of Modern Balinese poetry lies in the use of Balinese figures of speech and symbols rich in cultural meaning. Based on this gap, this study aims to examine the Balinese symbols in the poetry collection Adi Bulan by I Putu Wahyu Santosa and analyze their relevance in learning to appreciate Modern Balinese poetry. This research problem is formulated into two, (1) How is the representation of Balinese language symbols in the collection of Balinese poetry "Adi Bulan" by I Putu Wahyu Santosa?; and (2) What is the relevance in learning modern Balinese poetry appreciation?. This study uses primary data sources obtained from modern Balinese poetry collections obtained from the Balinese poetry collection book entitled "Adi Bulan" by I Putu Wahyu Santosa. Data collection was carried out through interviews and literature studies through data collection using reading and note taking techniques. The results obtained from this study indicate that there are 23 symbols of the Balinese language in the collection of Balinese poetry book "Adi Bulan" by I Putu Wahyu Santosa including: Balinese language symbol "bulan", "akah", "sunia", "damar", angin", "pertiwi", "toya", "gita", "segara", "candhi", "atma", "purnama", "dupa", "suarga", "surya", "danyuh", "ambara", "aksara", "sunari", "sandikala", "urip", "ngulah pati", and "paksi". In addition to the symbols of the Balinese language, this study also shows its relevance in learning modern Balinese poetry appreciation for all circles of the general public. The relevance is very close and important because learning about modern Balinese poetry appreciation will make it easier for someone to appreciate literary works, especially modern Balinese poetry literature.